Fear of violence and street harassment: accountability at the intersections - Logan, Laura S. (Kansas State University, 2013)
Feminists and anti-violence activists are increasingly concerned about street harassment. Several scholars, journalists and activists have documented street harassment during the last two centuries, and the recent development of organizations such as Hollaback! and Stop Street Harassment, as well increased attention from mainstream and feminist press, suggests street harassment is a serious social problem worthy of empirical investigation. In this dissertation, I focus on street harassment, fear of violence, and processes of doing gender. I take an intersectional approach to understand the relationships between gender, race, and sexuality, street harassment, fear, and social control. Furthermore, I investigate how accountability to being recognizably female is linked to street harassment and fear of crime for lesbians and other queer women. Drawing on semi-structured interviews with thirty white and women of color lesbians and bisexuals, I explore street harassment experiences, perceptions of fear and risk, and strategies for staying safe from the perspectives of queer women in rural, suburban, and urban locations in the Midwest. I discuss several key findings. First, there are distinct links between “doing gender” and the types of harassment these women experience, as well as links between “doing gender “and the types of assault they fear. Second, race matters - institutional violence shapes the fears and safety strategies of the queer women of color in my sample, and white privilege affects women’s willingness to consider self-defense in response to their fears. Finally, responses to fear and street harassment are shaped by the incite/invite dilemma. The incite/invite dilemma describes the predicament women face during street harassment encounters when they try to avoid responses that might incite escalated violence while also avoiding responses that might be viewed as an invitation for more aggressive harassment. This study extends research on accountability and doing gender, street harassment, fear of rape, and the gender differential in fear of crime. There are several practical implications of these findings. Chief among them is the need for activists and scholars to be attentive to the ways in which racism and racial inequality shape street harassment for women of color. In addition, feminists who work to end street harassment should broaden their focus to include a host of other pressing issues that influence the severity of and risks connected to street harassment for members of queer communities and communities of color. There are also theoretical implications for the theory of doing gender. Knowledge about accountability to sex category remains incomplete. Findings suggest the need to further investigate processes of accountability to sex category, with particular attention to diverse arrangements of orientations to sex category, presumptions about sex category, race, and queer gender identities.
Keywords: Street harassment; Fear of rape; Doing gender; Intersectionality; Victimization; Gender and sexuality; Gender Studies (0733); GLBT Studies (0492); Sociology (0626)